2019
DOI: 10.1016/j.seizure.2019.02.022
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma concentration and clinical effects of perampanel—The Kork experience

Abstract: A B S T R A C TPurpose: To investigate the correlation between steady-state plasma concentrations of perampanel (PER) with efficacy and tolerability in adult patients with difficult-to-treat epilepsy. Methods: PER plasma concentrations were assessed at steady-state conditions in 92 adult patients (57% female, 43% male, mean age 39,5 years, age range 20-73 years). All patients had been treated with PER at a stable dose for at least 3 weeks. Clinical efficacy was assessed on the day of measuring the plasma conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 19 publications
6
29
1
Order By: Relevance
“…In our previous study of perampanel treatment in 215 patients [3], the mean serum concentration in the 21 patients who achieved better outcomes was 450 ng/mL. In contrast, Steinhoff et al [10] evaluated 92 adult patients and found no significant differences between the plasma levels of responders and nonresponders.…”
Section: Introductionmentioning
confidence: 82%
“…In our previous study of perampanel treatment in 215 patients [3], the mean serum concentration in the 21 patients who achieved better outcomes was 450 ng/mL. In contrast, Steinhoff et al [10] evaluated 92 adult patients and found no significant differences between the plasma levels of responders and nonresponders.…”
Section: Introductionmentioning
confidence: 82%
“…In detail, data obtained from the clinical trial phase 3 showed that patients treated efficiently with Perampanel show a blood concentration in the range from 212 to 358 ng/mL (0.61–1.01 µM, with a 4 mg daily dose) and from 275 to 456 ng/mL (0.79–1.31 µM, with a 6 mg daily dose) 38 , 39 . Recent clinical data showed an even broader range of required blood levels of Perampanel to achieve effectiveness in patients 40 , 41 . Since more than 90% of Perampanel is bound by proteins 38 , 39 , the free Perampanel blood concentration is in the nanomolar range indicating that human brain AMPA receptor activity must be effectively modulated by Perampanel concentration in the nanomolar range.…”
Section: Discussionmentioning
confidence: 99%
“…However, a reliable therapeutic range for the plasma concentration of perampanel has not been established because individual reference ranges vary widely [11]. According to previously reported data [12], in 92 adult patients at steady state, the mean overall plasma concentration of perampanel was 323.5 ng/mL. The corresponding mean dose was 7.5 mg (range 2–12 mg).…”
Section: Discussion/conclusionmentioning
confidence: 99%